Secular ethics, east and west - TAN, Sor-hoon (Institutional Knowledge at Singapore Management University, 2017)
One can find secular ethics in Aristotle’s philosophy; one can also find secular ethics in Confucianism. Debates about the religious status of Confucianism date back several centuries and continue today. Ethical concepts in the Classical Confucian texts and the ethical life they advocate can be accepted on their own, independent of any otherworldly religious beliefs. This chapter reconstructs a Confucian secular ethics from the textual resources of Classical Confucianism—Analects, the Mencius, and the Xunzi. It then considers possibilities for reconciling ethics, science, and religion within secular Confucian perspectives by comparing two modern treatments of Confucian ethics, one inspired by Immanuel Kant and the other by sociobiology and evolutionary psychology. Finally, a third treatment is presented: a pragmatist treatment of Confucian secular ethics based on John Dewey’s reconstruction of the religious.